POTENSI DAUN JATI DAN DAUN KEMANGI SEBAGAI BAHAN AKTIF ANTISEPTIK PADA HAND SANITIZER - Aulia Firda Salsabila; Yolanda Nura Izzaty (GEMA KESEHATAN, 2021)
Along with the development of science and technology with the proliferation of instant products that are so fast and practical, an innovative product for hand sanitizer without water has emerged, namely, hand sanitizer. Hand sanitizer contains 60-95% alcohol which can kill microbes. However, Indonesia's availability of natural ingredients has not been used optimally, especially teak leaves and basil leaves. Teak leaves and basil leaves can be used as hand sanitizers. Teak is a plant that produces ethanol with the potential to be antibacterial with the content of flavonoid compounds, saponins, and tannins. Basil leaves have the main content of essential oil, which can be antibacterial. Basil leaves also have a distinctive natural aroma that can increase the value of the hand sanitizer products made. The purpose of writing this scientific article is to find out the potential of teak (Tectona grandis L.) and basil leaves (Ocimum basilicum L.) as antiseptic hand sanitizers to kill bacteria. This study uses a narrative review method. Data sources were obtained through an online database with antiseptic teak leaves and basil leaves on Google Scholar, Garuda, OneSearch, Scient Direct, and Research Gate. Data related to teak leaves and basil leaves that have been obtained from scientific journals and articles are presented through a descriptive approach to be compared and analyzed to get results relevant to the purpose of scientific papers. The results of previous studies related to basil leaves showed that the volatile oil formulation on aroma and appearance tests had good information, did not sting, and was attractive, and met the requirements for homogeneity, pH, organoleptic and irritation tests. Meanwhile, teak leaves contain secondary metabolites such as alkaloids, flavonoids, anthraquinones, tannins, naphthoquinone, cyanidin, and anthocyanins, which have various activities as antibacterial, antitoxic, and antioxidant activity, are effectively used as antiseptic active ingredients. The utilization of teak leaves and basil leaves as antiseptic ingredients in hand sanitizers can inhibit and kill germs in preventing disease and bacterial infection.